2006
DOI: 10.2174/157339506776843033
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Apoptosis by Gram-Positive Bacteria: Mechanistic Diversity and Consequences for Immunity

Abstract: Apoptosis, or programmed cell death (PCD), is an important physiological mechanism, through which the human immune system regulates homeostasis and responds to diverse forms of cellular damage. PCD may also be involved in immune counteraction to microbial infection. Over the past decade, the amount of research on bacteria-induced PCD has grown tremendously, and the implications of this mechanism on immunity are being elucidated. Some pathogenic bacteria actively trigger the suicide response in critical lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 413 publications
(569 reference statements)
1
40
0
Order By: Relevance
“…A novel function of secreted GBS GAPDH as an inducer of macrophage apoptosis also has been shown recently (76). Induction of apoptosis represents a possible mechanism of immune suppression by GBS, as occurs for other Gram-positive pathogens (77). Although the role of GM-CSF in macrophage responses to GBS appears to be beneficial for bacterial killing, studies are now required to define its role in macrophage antimicrobial responses in the GBS-colonized genital tract (e.g., the F4/80 + cell response).…”
Section: Discussionmentioning
confidence: 87%
“…A novel function of secreted GBS GAPDH as an inducer of macrophage apoptosis also has been shown recently (76). Induction of apoptosis represents a possible mechanism of immune suppression by GBS, as occurs for other Gram-positive pathogens (77). Although the role of GM-CSF in macrophage responses to GBS appears to be beneficial for bacterial killing, studies are now required to define its role in macrophage antimicrobial responses in the GBS-colonized genital tract (e.g., the F4/80 + cell response).…”
Section: Discussionmentioning
confidence: 87%
“…Gram-positive pathogens known to modulate apoptosis in host cells include Streptococcus, Staphylococcus, Bacillus, Listeria, and Clostridia species, although there appears to be limited conservation of the mechanisms involved (35). Among those more closely related to Enterococcus, group A streptococcus (GAS) induces rapid, dose-dependent apoptosis in primary and cultured macrophages and neutrophils, and it has been shown that the pore-forming cytolysin streptolysin O is necessary and sufficient for the apoptosis-inducing phenotype (36).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine and chemokine receptor gene expression, including that of Cxcl10 (25.4, 0.006), Cxcl5 (4.27, 0.071), Cxcl9 (3.99, 0.075), and Ccl12 (2.9, 0.078), was also prominent. Other responses of note were related to apoptosis regulators and effectors, including PARP family members 9 (2.8, 0.058), 12 (2.5, 0.053), and 14 (3.1, 0.088), CARD 5 (3.0, 0.035), and neutrophil apoptosis (3.3, 0.093), given the ability of GBS to induce apoptosis and PARP cleavage (79). Unexpectedly, several key defense molecules associated with GBS in other (non-UTI) infection models such as inducible nitric oxide synthase (iNOS) (78) and TNF-␣ (27) were not detected as significantly altered in expression in the bladder transcriptome.…”
Section: Gbs Bladder Transcriptomementioning
confidence: 99%